Introducing e-developers to support a university's blended learning developments - ann Ooms; Linda Burke; Tim Linsey; Celayne Heaton-Shrestha (Association for Learning Technology, 2008)
Introducing technology in higher education raises questions about staff roles and the organisation of development practices. This article presents the findings from a case study that was undertaken to evaluate the effectiveness of introducing three centrally supported e-developers to work with academic teams to provide specialist support. The e-developer role is explained, and related to existing literature about learning technologists. The case illustrates how the e-developers worked collaboratively with academic staff and the perceptions of the academic staff, e-developers and educational technology leaders of the e-developer model used in a university in southwest London. The findings offer an opportunity to understand this kind of role, and the value of a model of staff development that does not involve taking academic staff out of the teaching area to become e-developers. The model supports ‘situative' professional development, which helps promote technology integration into teaching and suggests that e-developers provided cost-effective mentorship which participants believed would have a positive impact on student learning.